The role of the pharmacist in Primary Care: Understandings from the perspective of pharmaceutical care (Research, Society and Development, 2023)
Introduction: The role of the pharmacist, for a long time, was restricted to dispensing medicines. Nowadays, it is clear that this is no longer the only function of this professional, who takes on a much more active role in integrating multidisciplinary teams and in patient care, through pharmaceutical care. Objective: Based on this research project, it is proposed to verify the main gaps and difficulties encountered in the work of pharmacists in the primary care component. Methodology: Narrative review of literature based on articles published on the academic research platforms Lilacs, Scielo and BVSalud between 2017 and 2023, to carry out research that highlights the possibilities for pharmacists to work in primary care and the main difficulties still encountered. Results and discussion: Among the main difficulties faced by pharmacists when working in Primary Care are work overload, difficulty in integrating multidisciplinary teams, lack of professional appreciation, scarcity of resources to carry out actions and lack of training so that professionals can act effectively in this component, promoting prevention and recovery of public health. Conclusion: Despite the challenges, it is clear that the pharmacist's role in primary care is much more active and participatory, especially in promoting public health, which demonstrates that this professional is a fundamental player in multidisciplinary action in this component.